Laboratory study on the leaching potential of spent alkaline batteries - Susana M. Xará (2009)
Four different leaching tests were carried out with spent alkaline batteries as an attempt to quantify the environmental potential burdens associated with landfilling. The tests were performed in columns filled up with batteries either entire or cross-cut, using either deionized water or nitric acid solution as leachant. In a first set of tests, the NEN 7343 standard procedure was followed, with leachant circulating in open circuit from bottom to top through columns. These tests were extended to another leaching step where leachant percolated the columns in a closed loop process. Leachate solutions were periodically sampled and pH, conductivity, density, redox potential, sulphates, chlorides and heavy metals (As, Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Sb, Tl and Zn) were determined in the samples. The results showed that the total amount of substances leached in tests with cross-cut batteries was higher than with entire ones; zinc and sulphates were the Substances found the most in the leachate solutions. In general, the amount of substances dissolved in open circuit is higher than in closed loop due to the effect of solution saturation and the absence of fresh solution addition. Results were compared with metal contents in the batteries and with legal limits for acceptance in landfill (Decision 2003/33/CE and Decree-Law 152/2002). None of the metals were meaningfully dissolved comparatively to its content in the batteries, except Hg. Despite the differences in the experiment procedure used and the one stated in the legislation (mixing. contact time and granulometry), the comparison of results obtained with cross-cut batteries using deionized water with legal limits showed that batteries Studied Could be considered hazardous waste.